The cloud that wanted to be: (a mouth full of shadows) (REVISTA NODO, 2025)
This project is intended as an exploration of the speculative nature of images generated by Artificial Intelligence (AI) while reflecting on the fragility and malleability of personal memory. To date, the project consists of two pieces: The Cloud I Wanted to Be (a Mouth Full of Shadows) and Every Time We Talk Less About the Child I Was.
Keywords: AI; Images; Artifical; Childhood